CARACTERIZAÇÃO MORFOLÓGICA DE FIBRAS DE ESPÉCIES FLORESTAIS - RIBEIRO, Odair Alves; RIBEIRO, Eliane Alves; COSTA, Emerson Belarmino; ZENTENO FILHO, Arnaldo Ramão; GOUVÊA, Adriana de Fátima Gomes (ANAIS DO ENIC, 2020)
-